2014
DOI: 10.5539/ijbm.v9n3p185
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Work-Related Communication in the UAE: A Qualitative Study

Abstract: Abstract•Purpose-The purpose of the research is to investigate the true nature of any differences between men and women, in the way that they communicate at the workplace.•Design/methodology/approach-A qualitative research was carried out using semi-structured interview questions, involving 418 UAE nationals comprising of 218 Emirati males and 200 Emirati females ranging from the age of 20 years to 55 years.•Findings-Findings partially supported Tannen (1990) and Gray (1992), but also had some new interesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…While most students felt encouraged to ask questions, some were hesitant due to unfamiliarity with staff members or shyness, especially with male staff nurses. The UAE culture is conservative, and women in this culture may feel shy in group communication, and they may either be silent or prefer to find a female to talk to ( Ahmad, 2014 ). Moreover, feeling unintegrated into ward teams was a hindrance to clinical learning, and this could be attributed to students’ temporary assignments to these wards or the nurses’ demanding schedules and their inability to provide adequate support ( Ford et al, 2016 ; Thomas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While most students felt encouraged to ask questions, some were hesitant due to unfamiliarity with staff members or shyness, especially with male staff nurses. The UAE culture is conservative, and women in this culture may feel shy in group communication, and they may either be silent or prefer to find a female to talk to ( Ahmad, 2014 ). Moreover, feeling unintegrated into ward teams was a hindrance to clinical learning, and this could be attributed to students’ temporary assignments to these wards or the nurses’ demanding schedules and their inability to provide adequate support ( Ford et al, 2016 ; Thomas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emirati female participants' reluctance to accept the request may stem from "social forces [that] sometimes prevent women from interacting in public with men outside their families" (Dariela et al 2017: 4). Past research found that communication between genders in the UAE is normally permissible at work as long as it is on work-related matters; however, purely social interaction between men and women especially outside of the workplace could be seen by some as contrary to Emirati customs and the religion of Islam (Ahmad 2014). In the case of a photo taken with a stranger, the situation may be even more controversial.…”
Section: Discussionmentioning
confidence: 99%
“…https://www.globalmediainsight.com/blog/uae-population-statistics/ There indeed is empirical evidence that differences exist between male and female Emirati speakers' overall communication styles and linguistic tendencies. About the former, Ahmad (2014) points to several differences. In comparison to Emirati women, Emirati men are more direct and to the point and less hesitant to share opinions.…”
Section: Introductionmentioning
confidence: 99%